THE RELATIONSHIP BETWEEN PHYSICAL FITNESS AND ACADEMIC PERFORMANCE IN UNIVERSITY STUDENTS: A CORRELATIONAL STUDY (University Arena, 2025)
Background. In recent years, increasing attention has been paid to the connection between physical activity and cognitive performance, especially in the academic context. The sedentary lifestyle of university students has raised concerns regarding both physical health and academic success. Previous research suggests that regular physical activity can enhance cognitive functions such as memory, attention, and executive control.Objectives. The purpose of this study was to explore the relationship between physical fitness and academic performance among undergraduate students from the University of Bucharest. The research aimed to determine whether higher fitness levels are associated with better academic outcomes.Methods. The study was conducted on a sample of students aged 19–21 who attended mandatory physical education classes. Physical fitness was assessed at the end of the first semester using standardized field tests: the Harvard Step Test (cardiorespiratory endurance), push-ups in 30 seconds (upper-body strength), sit-ups in 30 seconds (core endurance), and the Sit & Reach test (flexibility).Academic performance was measured based on students’ final grade point averages (GPA). A lifestyle questionnaire regarding sleep, study habits, and perceived energy levels was also applied. Statistical analyses included descriptive statistics and correlation tests (Pearson/Spearman) between physical fitness scores, questionnaire responses, and GPA.Results. Preliminary observations indicate that the overall fitness levels of participants were below the age-related average, particularly in cardiorespiratory endurance. A positive correlation is expected between higher physical fitness scores and higher academic  performance, particularly in students who reported regular physical activity outside of class and better sleep habits.Conclusion. This study highlights the potential impact of physical fitness on students’ academic success. Promoting physical activity within university curricula may contribute to improved cognitive functioning and better academic outcomes. Further analysis will determine the strength and significance of these associations.
Keywords: physical fitness; academic performance; university students; cardiorespiratory endurance; cognitive function